Trade flow of manufacturing sector and foreign direct investment in ASEAN economic integration: the gravity model of trade - Diah Wahyuningsih (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2021)
This study aims to determine the effects of ASEAN economic integration on the manufacturing sector's trade flow and foreign direct investment. This study using panel data regression. The results show that ASEAN economic integration affects trade in the manufacturing sector and foreign direct investment (FDI) in ASEAN member countries. The tariff elimination policy increased trade flows in the manufacturing sector and foreign direct investment. The variable of GDP has a positive and significant effect on the manufacturing sector's trade flows and foreign direct investment. Exchange rate variables have a negative and significant effect on trade flows in the manufacturing sector and foreign direct investment. Meanwhile, the distance variable negatively affects trade in the manufacturing sector, but it does not affect foreign direct investment.